Hypocholesterolemic effect of consumption of oats (Avena sativa) in a group of adults Chaclacayo, 2015 - Rodríguez Pérez, Noelia (2019)
Objective: Determine the effect of the consumption of oats (Avena sativa) on the level of cholesterol and triglyceridesin serum. Methodology: Quantitative approach, preexperimental design (pre and post) and longitudinal cut. Thesample was formed by 26 adults of the Nueva Alianza-Chaclacayo, both enders, between 28 to 80 years old,with cholesterol levels > a 190mg/dl, who were selected by sampling non-probability of intentional kind. Theconsumption was 60 g of oat flakes for 6 weeks. Results: Showed statistically significant reduction in cholesterollevels (T= 4, 95; <.05) of 217,04 mg/dl a 195,73 mg/dl. However, there were no statistically significant changesin the level of triglycerides (Z= -1, 18; p>.05). Conclusion: In conclusion, the consumption of 60 g of oat flakesover a 6 week period significantly reduces the level of total cholesterol.